2020
DOI: 10.1116/1.5142012
|View full text |Cite
|
Sign up to set email alerts
|

Spatially controlled stem cell differentiation via morphogen gradients: A comparison of static and dynamic microfluidic platforms

Abstract: The ability to harness the processes by which complex tissues arise during embryonic development would improve the ability to engineer complex tissuelike constructs in vitro—a longstanding goal of tissue engineering and regenerative medicine. In embryos, uniform populations of stem cells are exposed to spatial gradients of diffusible extracellular signaling proteins, known as morphogens. Varying levels of these signaling proteins induce stem cells to differentiate into distinct cell types at different position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…208 Additionally, microfluidic systems can be designed to create signaling gradients within a culture to spatially influence cell response or development. For example, Cui et al 209 demonstrated regionalized formation of the primitive streak from pluripotent stem cells within a device using controlled microfluidics. This same approach could be applied to developmental models to optimize differentiation or maturation conditions, differentiate co-cultures within a device, or for downstream evaluation of various drug concentration gradients.…”
Section: Features Of Microfluidic Cellular Systems For Cardiomyocyte mentioning
confidence: 99%
“…208 Additionally, microfluidic systems can be designed to create signaling gradients within a culture to spatially influence cell response or development. For example, Cui et al 209 demonstrated regionalized formation of the primitive streak from pluripotent stem cells within a device using controlled microfluidics. This same approach could be applied to developmental models to optimize differentiation or maturation conditions, differentiate co-cultures within a device, or for downstream evaluation of various drug concentration gradients.…”
Section: Features Of Microfluidic Cellular Systems For Cardiomyocyte mentioning
confidence: 99%
“…Three dimensional (3D) printing, or additive manufacturing (AM), is touted as the next generation of agile, efficient manufacturing technology with the ability to fabricate complex structures for applications ranging from inexpensive rapid prototyping to tissue engineering for regenerative medicine. [1][2][3] Unfortunately, most AM processes introduce micrometer-scale anisotropic inhomogeneities in chemical, thermal, and mechanical properties, causing the performance of fabricated parts to depend strongly and unpredictably on printing conditions. [4,5] Without full understanding of how AM parameters affect mechanical properties, AM will have limited societal impact.…”
Section: Introductionmentioning
confidence: 99%